Conceptual approaches to vocational and tourism training of teachers in higher education institutions - L.J. Dudorova (Physical Education of Students, 2013)
Considered the direction of teacher’s training based on the model of a competent graduate. It is formed the criteria of the faculty of the institute of physical education and sports and the possibility of their selection. It is noted that a teacher must possess modern technologies of general and vocational education, a set of effective methods and techniques sufficient professional knowledge to provide education of future professionals (teaching, planning and management of the didactic and educational systems). It is recommended the formation of the teaching staff to consider the following: to conduct a competitive selection of teachers with experience teaching physical education and sports, coaching and tourism. Teachers also need training from the best graduates of the institute of physical education and sport.